EFEK VARIASI PERBANDINGAN KOMPOSISI PEREKAT RESIN LIMBAH GERGAJIAN KAYU JABON (Anthocephalus cadamba) DAN KAYU SENGON (Paraserianthes falcataria) TERHADAP SIFAT FISIKA DAN MEKANIKA PAPAN PARTIKEL - Khoiril Mustofa; Kurdiansyah Kurdiansyah; Gusti Akhmad Rahmad Thamrin (Universitas Lambung Mangkurat, 2020)
The purpose to analyze the physical properties of moisture content, density, shrinkage and development of thickness and mechanical properties (MoE and MoR) of wood particle board jabon (Anthocephalus cadamba) and sengon wood (Paraserianthes falkataria). The study was conducted in February-May 2019. Test specimens were made from jabon sawn wood and sengon wood with polyester resin as many as 18 pieces with 15 pieces for tensile test and 3 pieces for hardness test. Standard testing based on SNI 03-2105-2006 such as physical and mechanical properties of particle board in the form of water content, density, thickness development, shrinkage, flexural firmness (Modulus of Elasticity or MOE) and broken firmness (Modulus of Rupture or MOR). Physical properties The particle board with epoxy resin jabon and sengon wood powder adhesive has fulfilled SNI 03-2105-2006 with a moisture content value ranging from 9.60% - 13.00%, the density value on adhesive is 30% and 40% (B2 and B3), shrinkage ranges 1.11% - 2.86% and thick development of 14.32% - 19.82%. The mechanical properties of particle board with epoxy resin adhesives of jabon and sengon wood powder did not meet SNI 03-2105-2006 with flexural firmness (Modulus of Elasticity or MOE) 1,477.44 kgf / cm²-1,751.45 kgf / cm and broken firmness value (Modulus of Rupture or MOR) ranges from 16.12 kgf / cm² - 25.90 kgf / cm².Keywords: sawn waste; physical properties; mechanical properties